Deformed Honeycomb Lattices of InGaAs Nanowires Grown on Silicon‐on‐Insulator for Photonic Crystal Surface‐Emitting Lasers. Issue 5 (20th December 2022) - Messina, Cristian; Gong, Yongkang; Abouzaid, Oumaima; Ratiu, Bogdan‐Petrin; Grieb, Tim; Yan, Zhao; Rosenauer, Andreas; Oh, Sang Soon; Li, Qiang
Abstract: Photonic crystals can be used to achieve high‐performance surface‐emitting lasers and enable novel photonic topological insulator devices. In this work, a GaAs/InGaAs heterojunction nanowire platform by selective area metalorganic vapor phase epitaxy for such applications is demonstrated. The nanowires are arranged into deformed honeycomb lattices on silicon‐on‐insulator substrate to exploit the quadrupolar photonic band‐edge mode. Core–shell and axial heterostructures are formed with their crystalline properties studied by scanning transmission electron microscopy. Room‐temperature, single mode lasing from both stretched and compressed honeycomb lattices within the telecom‐O band, with lasing threshold as low as 1.25 µJ cm −2 is demonstrated. The potential of using InGaAs nanowire‐based honeycomb lattices for small‐divergence surface‐emitting lasers and topological edge mode lasers is investigated. Finite‐difference time‐domain far field simulations suggest a sub‐10° beam divergence can be achieved thanks to the out‐of‐plane diffraction. Abstract : A bottom‐up InGaAs nanowire platform on silicon‐on‐insulator for photonic crystal surface‐emitting lasers at telecom wavelengths is presented. The nanowires are arranged into deformed honeycomb lattices using lithographically defined selective area epitaxy. Room‐temperature, low threshold lasing from both stretched and compressed honeycomb lattices is demonstrated. The potential of using the InGaAs nanowire‐based honeycomb lattices for topological cavity lasers is discussed.